CRISPR–Cas12‐based field‐deployable system for rapid detection of synthetic DNA sequence of the monkeypox virus genome. Issue 1 (23rd December 2022) - Chen, Qun; Gul, Ijaz; Liu, Changyue; Lei, Zhengyang; Li, Xingyu; Raheem, Muhammad A.; He, Qian; Haihui, Zhang; Leeansyah, Edwin; Zhang, Can Y.; Pandey, Vijay; Du, Ke; et al.
Abstract: The global outbreak of the monkeypox virus (MPXV) highlights the need for rapid and cost‐effective MPXV detection tools to effectively monitor and control the monkeypox disease. Herein, we demonstrated a portable CRISPR–Cas‐based system for naked‐eye detection of MPXV. The system harnesses the high selectivity of CRISPR–Cas12 and the isothermal nucleic acid amplification potential of recombinase polymerase amplification. It can detect both the current circulating MPXV clade and the original clades. We reached a limit of detection (LoD) of 22.4 aM (13.5 copies/µl) using a microtiter plate reader, while the visual LoD of the system is 75 aM (45 copies/µl) in a two‐step assay, which is further reduced to 25 aM (15 copies/µl) in a one‐pot system. We compared our results with quantitative polymerase chain reaction and obtained satisfactory consistency. For clinical application, we demonstrated a sensitive and precise visual detection method with attomolar sensitivity and a sample‐to‐answer time of 35 min.